Upaya Meningkatkan Kemampuan Guru dalam Menggunakan Model Pembelajaran Melalui Supervisi Klinis di SD Negeri 168/X Pandan Sejahtera Tanjung Jabung Timur - Sukanto Sukanto (Journal on Education, 2021)
This study aims to disclose information and discuss the Efforts to Improve Teacher Ability in Using Learning Models through Clinical Supervision at SD Negeri 168/X Pandan Sejahtera Tanjung Jabung Timur. This research is included in the type of school action research (PTS). This research was carried out in this research was carried out at SD Negeri 168/X Pandan Sejahtera. The time of this research was carried out in the odd semester of the 2021 - 2022 school year, which began in July 2021. The subjects in this study were 8 teachers of SD Negeri 168/X Pandan Sejahtera. The research procedure consisted of two cycles with four stages of research starting from planning, implementing, observing and reflecting. Data collection in this study was carried out using instruments, observations and documents. The data were analyzed using the percentage formula. The results of this study indicate that clinical supervision can improve the ability of teachers in using the learning model of SD Negeri 168/X Pandan Sejahtera which is marked by an increase from pre-cycle, cycle I, cycle II.